SERASIM: 3-D Expert System For Greenhouse Design - Bora Şen; Sevilay Topçu; Özkan Güğercin; Hasan Hüseyin Öztürk (Turkish Journal of Agriculture: Food Science and Technology)
Greenhouse construction projects need to consider local climate characteristics, production type in the greenhouse and materials used for the physical structure and glazing. A major share of commercial greenhouse manufacturers in Turkey produce turnkey greenhouse projects either using by trial and error method or imitating/reproducing greenhouse imported from other countries. Improperly designed projects may result in greenhouses having weak construction or more expensive structures due to using unnecessarily larger profiles which consequently cause a loss the profits for the growers. This study aims to contribute to the improvements and overcome the gaps in practice of greenhouse projects by designing a software for an expert system that utilizes an accurate Project considering them and mandatory buildings standards of Turkish Standardization Institute (TSE). The expert system, named SERASİM, has been developed within the framework of the present MSc. Thesis and enables calculating each part of the construction system of a gable roof glass house according to TSE standards. Besides calculations for statics, dynamics and strength as well estimating the bill of quantity, SERASİM can be utilized to determine the heating requirements and costs for selected locations and crops. SERASİM may also be used as a teaching tool for courses including greenhouse design, protected cultivation and greenhouse acclimatization.